Temporal stability of forest productivity declines over stand age at multiple spatial scales - Rongxu Shan; Ganxin Feng; Yuwei Lin; Zilong Ma (Nature Communications)
Abstract There is compelling experimental evidence and theoretical predictions that temporal stability of productivity, i.e., the summation of aboveground biomass growth of surviving and recruitment trees, increases with succession. However, the temporal change in productivity stability in natural forests, which may undergo functional diversity loss during canopy transition, remains unclear. Here, we use the forest inventory dataset across the eastern United States to explore how the temporal stability of forest productivity at multi-spatial scales changes with stand age during canopy transition. We find that productivity stability decreases with stand age at the local and metacommunity scales. Specifically, consistent declines in local diversity result in less asynchronous productivity dynamics among species over succession, consequently weakening local stability. Meanwhile, increasing mortality and the transition from conservative to acquisitive species with succession weaken species and local stability. Successional increases in species composition dissimilarity among local communities cause more asynchronous productivity dynamics among local communities. However, the decline in local stability surpasses the rise in asynchronous productivity dynamics among local communities, resulting in lower metacommunity stability in old forests. Our results suggest lower productivity stability in old-growth forests and highlight the urgency of protecting diversity at multiple spatial scales to maintain productivity stability.